2000
DOI: 10.1046/j.1365-2249.2000.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Th1 cytokine pattern in sarcoidosis is expressed by bronchoalveolar CD4+ and CD8+ T cells

Abstract: SUMMARYThe pathogenesis of pulmonary sarcoidosis has been related to an increased production of Th1-like cytokines. However, cytokine expression in sarcoidosis has not been systematically studied at a singlecell level. We therefore investigated the expression of IL-2, IL-4, IL-13, tumour necrosis factor-alpha (TNF-a ) and interferon-gamma (IFN-g) intracellularly in bronchoalveolar lavage (BAL) and peripheral blood CD31 T lymphocytes from patients with pulmonary sarcoidosis (radiologic stage II±III, n 8) and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
67
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 34 publications
(50 reference statements)
4
67
0
3
Order By: Relevance
“…The pattern of T-cell cytokine production is indicative of sarcoidosis being a T-helper cell-1-mediated disease [12,32]. Although no significant T-cell immunoreactivity for TNF-a was observed, a recent study reported that increased fractions of T-cells, which intracellularly expressed TNF-a, were observed by fluorescence activated cell sorting (FACS) in BAL but not in peripheral blood of sarcoidosis patients compared with control subjects [11]. On the contrary, another study using FACS failed to detect any significant difference between sarcoidosis patients and healthy controls in the frequency of T-cells that intracellularly expressed TNF-a [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of T-cell cytokine production is indicative of sarcoidosis being a T-helper cell-1-mediated disease [12,32]. Although no significant T-cell immunoreactivity for TNF-a was observed, a recent study reported that increased fractions of T-cells, which intracellularly expressed TNF-a, were observed by fluorescence activated cell sorting (FACS) in BAL but not in peripheral blood of sarcoidosis patients compared with control subjects [11]. On the contrary, another study using FACS failed to detect any significant difference between sarcoidosis patients and healthy controls in the frequency of T-cells that intracellularly expressed TNF-a [13].…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous release of TNF-a [8], interleukin (IL)-1 [9], and IL-2 [10] by activated macrophages and T-cells is considered pivotal to the formation of immune granulomas. Activated T-cells may also contribute to the release of pro-inflammatory cytokines like TNF-a into the BAL fluid [11][12][13]. In addition, pulmonary epithelial cells, which are able to act as accessory cells in T-cell activation, and in immunoregulation cells of the lung [14] may also release TNF-a under certain conditions [15][16][17].…”
mentioning
confidence: 99%
“…Animal model studies of interstitial fibrosis using bleomycin, silica, and thoracic irradiation support these conclusions (16 -18). In contrast, expression of the Th1 cytokine, IFN-␥, has been found to be reduced or absent in IPF yet is prominent in granulomatous lung disorders such as sarcoid (13,19,20). These findings are consistent with previous observations that IFN-␥ 1) inhibits IGF-I production by macrophages (21), 2) inhibits collagen synthesis by fibroblasts (22), 3) is efficacious in ameliorating pulmonary fibrosis in the bleomycin model in mice (23), and 4) modestly improves pulmonary function and survival in IPF patients (24).…”
mentioning
confidence: 99%
“…CD4+ T-lymphocytes are divided into two subgroups, T helper (Th)1 and Th2 cells, on the basis of cytokine production [5]. Based on the Th1/ Th2 paradigm, sarcoidosis is considered a typical Th1-dominant disease, since T-lymphocytes in bronchoalveolar lavage fluid (BALF) and lymph nodes from patients with sarcoidosis predominantly produce interferon (IFN)-c, interleukin (IL)-2 and tumour necrosis factor (TNF)-a or -b [6][7][8]. We and others have reported that levels of Th1 chemokines, including CXCL9/IFN-c (Mig), CXCL10/interferon-c-inducible protein-10 (IP-10) and CXCL11/interferon-inducible T-cell a-chemoattractant (I-TAC), were elevated in BALF of patients with sarcoidosis [9][10][11][12][13].…”
mentioning
confidence: 99%